Efektivitas Ekstrakurikuler Tahsin Al-Qur’an Dalam Meningkatkan Keampuan Membaca Al-Qur’an Siswa SMA Budi Satrya Medan - Azminur, Saipul; Dahlan, Zaini; Azhr, Ihsan Satrya (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the effectiveness of the Tahsin Al-Qur'an extracurricular program in improving the Quran reading skills of students at Budi Satrya High School, Medan. Using a qualitative approach with a case study design, this research involves students participating in the Tahsin program, mentors, and religious education teachers as primary informants. Data were collected through in-depth interviews, participatory observations, and analysis of related documents. The results of the study show that the Tahsin Al-Qur'an activity significantly improves the quality of students' recitation, particularly in the aspects of tajweed, makhraj, fluency, and understanding of Quranic texts. The interactive teaching approach, repeated practice methods, and personalized mentoring by instructors have proven effective in enhancing students' abilities. Supporting factors for the program's success include students' enthusiasm, mentors' commitment, and a conducive learning environment.The challenges identified include limited time, varying initial skill levels among students, and a lack of learning aids. In conclusion, the Tahsin Al-Qur'an extracurricular program is an effective initiative for improving Quran reading skills and shaping students' religious character. The study also provides recommendations for the management and development of the Tahsin program in schools as part of efforts to enhance religious education.